2010
DOI: 10.1128/aem.02756-09
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Phosphate Solubilization and Medicago Plant Yield by an Indole-3-Acetic Acid-Overproducing Strain of Sinorhizobium meliloti

Abstract: Nitrogen (N) and phosphorus (P) are the most limiting factors for plant growth. Some microorganisms improve the uptake and availability of N and P, minimizing chemical fertilizer dependence. It has been published that the RD64 strain, a Sinorhizobium meliloti 1021 strain engineered to overproduce indole-3-acetic acid (IAA), showed improved nitrogen fixation ability compared to the wild-type 1021 strain. Here, we present data showing that RD64 is also highly effective in mobilizing P from insoluble sources, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(63 citation statements)
references
References 40 publications
(46 reference statements)
4
55
0
2
Order By: Relevance
“…NGR234 (38). An increased level of IAA has been found to be good for rhizobium-legume symbiosis (37,75,76). In this study, the evolution pattern of y4wE was found to be similar to that of rhcJ and nod genes on pSymA.…”
Section: Discussionmentioning
confidence: 53%
“…NGR234 (38). An increased level of IAA has been found to be good for rhizobium-legume symbiosis (37,75,76). In this study, the evolution pattern of y4wE was found to be similar to that of rhcJ and nod genes on pSymA.…”
Section: Discussionmentioning
confidence: 53%
“…Primers used for the amplification of segments of pstS (DF090/DF091), pstB (DF092/DF093), smc00128 (DF094/DF095), and smc02641 (DF096/DF097) are listed in Table S2. The smc00128 and smc02641 genes were used as the reference standards (23,60), and the primers for these fragments were described previously (60). The R 2 value corresponding to the linear line of best fit through the points of each of the standards was always Ͼ0.99.…”
Section: Medium Phosphate Determinationmentioning
confidence: 99%
“…In addition, RD64 strain showed enhanced long-term cell survival (Defez, 2006), has improved nitrogen fixation ability (Bianco & Defez, 2010b;Imperlini et al, 2009) and is highly effective in mobilizing P from insoluble source such as Phosphate Rock . Mt-RD64 plants showed an higher degree of protection against oxidative damage induced by salt stress ) and significant increases in both the shoot and root fresh weight under P-starved condition when compared to salt-stressed and P-starved Mt-1021 plants (Bianco & Defez, 2010a). For Mt-RD64 plants we also observed a re-modulation of phytohormones, with a higher IAA content in nodules and roots and a decreased IAA levels in shoots, as compared with Mt-1021 plants.…”
Section: Discussionmentioning
confidence: 99%
“…Under P-limiting conditions, the IAA-overproducing RD64 strain showed high P-mobilizing activity that is connected to the synthesis of high levels of acid phosphatase enzymes and the secretion into the growth medium of malic, succinic, and fumaric acids in large quantities. As compared to Mt-1021 plants, Mt-RD64 plants released large amount of another P-solubilizing organic acid, 2-hydroxyglutaric acid and showed significant increase in both shoot and root fresh weights, when grown under P-deficient conditions (Bianco & Defez, 2010a).…”
Section: Enhancement Of Nutrients Up-takementioning
confidence: 99%